Policy analysis of independent curriculum in elementary schools - yulianti yulianti; Syamsul Hadi (Jurnal Bidang Pendidikan Dasar, 2023)
The purpose of this study is to analyze the policy of implementing the independent curriculum at the elementary school level. This type of research is qualitative with a literature study approach, using a descriptive method in presenting data collection from the keywords Independent Curriculum and Elementary School which was carried out in various online journal sources through Google Scholar. The results of the selection using 50 articles from national journals related to the independent curriculum in elementary school’s state that the essence of the Independent Curriculum is to set goals to provide space for each individual to grow and develop according to their unique nature, the implementation uses a differentiation approach to facilitate students so that their learning needs are met. Implementation of the Independent Curriculum according to the level of school or madrasah readiness through the willingness of the principal and teachers is the key to success.